Pemberdayaan Kader Lansia dalam Upaya Penatalaksanaan Hipertensi di Desa Bangun Rejo Tahun 2025 - Adelina Sembiring; Mastaida Tambun; Lisbet Gurning; Rosmega Rosmega; Petra Diansari Zega; Apriliani Kristina Gulo; Deo Cristian Meliala; Erika Adelia Turnip (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
Hypertension is one of the most common chronic diseases among the elderly and serves as a major risk factor for cardiovascular diseases. The management of hypertension not only relies on medical interventions but also requires active community participation, particularly from elderly health cadres. The objective of this activity is to empower elderly health cadres in the management of hypertension through education, training, and mentoring. The methods used include health education sessions, blood pressure measurement training, the development of monitoring schedules, and the distribution of educational leaflets. The results of the activity showed an increase in the knowledge of elderly cadres about hypertension, improved skills in blood pressure measurement, and a strengthened commitment to regularly monitor elderly individuals with hypertension. This initiative is expected to reduce the incidence of hypertension-related complications and enhance the quality of life of the elderly in Bangun Rejo Village